21. CHARACTERISTICS OF PATIENTS WITH PNEUMONIA CAUSED BY SARS - COV 2 TREATMENT AT THE RESPIRATORY DEPARTMENT OF THONG NHAT HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: Study the characteristics of pneumonia caused by SARS-CoV-2 admitted to the Respiratory Department at Thong Nhat hospital.Methods: Description, cross-sectional, case series. The study was conducted on 136 cases of confirmed pneumonia caused by SARS-CoV-2. Diagnosis of pneumonia caused by SARSCoV 2 was by chest X-ray and/or CT scan. Main results: SARS-CoV-2 pneumonia symptoms, clinical examination and blood tests, RT-PCR (reverse transcription polymerase chain reaction) results and chest X-ray results.Results: There were 80 (58.8%) men and 56 (41.2%) women, average age was 68.2 ± 10.5 and BMI 26.7 ± 6.2 kg/m2. Under 60 years old accounted for 35.3%; 60-70 years old 22.1%; 71- 80 years old 23.5% and > 80 years old only 10.1%. Common comorbidities were hypertension 42.6%; diabetes 40.4%; chronic lung disease 22.8%. Time from onset to pneumonia was about 7.5 ± 2.1 days. The number of people with bilateral pneumonia accounted for 72.1%. Common symptoms were fever, cough, breathing difficulty, digestive disorders, muscle pain, weakness and headache. Oxygen saturation, CRP and white blood cell count in the bilateral pneumonia group were 92.1 ± 2.3%; 81.5 ± 32.3 mg/L and 9 ± 2.4 103/mm3, respectively; were statistically significantly different compared to the unilateral pneumonia group. The rate of respiratory failure/mechanical ventilation, pulmonary embolism complications, long hospital stay and mortality rate were mainly in the group with bilateral pneumonia.Conclusion: Pneumonia caused by SARS-CoV-2 mainly has symptoms of fever, cough and breathing difficulty. Complications and death rates are high when bilateral pneumonia is present.
Keywords: SARS-CoV-2; pneumonia